Magnetic field measurement from 132 kv and 275 kv overhead transmission lines within residential area - Baharom, Md Nor Ramdon; Zainal, Zainab; Ullah, Irshad; Mahmod, Luqman Hakim (United Kingdom Simulation Society, 2016)
Overhead transmission line (OTL) has been around for so many years as one of the most important elements of electric power systems. Conductors, as being a part of the medium to transfer electricity through the OTL, produces electromagnetic field to its surrounding that have been a public concern for ages. OTL were meant to be built as far away from a population. Though from time to time, the OTL rights-of-way (ROW) were violated due to lack of space and rapid urbanization. This paper addresses the challenges faced during magnetic field level measurement within a residential area that was still under construction. EMDEX II Meter, Linear Data Acquisition System (LINDA) Wheel and Gauss Meter were used during the magnetic field measurements. Maximum magnetic field level data collected from measurement were presented.